Recent trends in the registration of blindness and partial sight in Leicestershire. Issue 2 (February 1989) - Thompson, J R; Du, L; Rosenthal, A R
Abstract : A study is reported of all new registrations for blindness and partial sight in the county of Leicestershire, England, for the years 1965, 1975, and 1985. The number of new registrations for blindness has risen considerably over this period, but the increase is shown to be attributable to changes in the age structure of the population and under-registration in 1965. The number of new registrations for partial sight has also increased over the study period but by significantly more than would be expected, even after changes in the population structure are allowed for. The registration rates for Leicestershire when analysed by age, sex, and cause are shown to be broadly in line with available national figures. Registration rates for macular degeneration and glaucoma are increasing in both males and females, and rates for cataract are at a significantly higher level for women than for men.